Engineering plastic phase transitions via solid solutions: the case of "reordering frustration" in ionic plastic crystals of hydroxyquinuclidinium salts. Issue 8 (19th May 2022) - Ocak, Samet; Birolo, Rebecca; Carì, Gianluca; Bordignon, Simone; Chierotti, Michele R.; Braga, Dario; Gobetto, Roberto; Salzillo, Tommaso; Venuti, Elisabetta; Yaffe, Omer; d'Agostino, Simone
Abstract : Reordering Frustration! Size and shape of the anions have been found to affect the order–disorder phase transition behavior in solid solutions-of ionic plastic crystals drastically. As a result, permanent plastic phases are obtained. Abstract : A family of salts of R -(+)-(3)-hydroxyquinuclidinium [QH] +, with SO4 2−, BPh4 −, BF4 − and PF6 − counter-anions, have been prepared by the metathesis of [QH]Cl and metal salts of the corresponding anions. Solid solutions of formula [QH](PF6 ) x (BF4 )1− x for x = 0.9, 0.8, 0.7 have also been obtained. The crystalline materials have been investigated by a combination of solid-state techniques, including variable temperature XRD, thermal analyses, multinuclear ( 11 B, 13 C, 15 N, 19 F, and 31 P) solid-state NMR spectroscopy, variable temperature wideline 19 F T 1 relaxation measurements, and micro-Raman spectroscopy to investigate their thermal stability and phase transition behaviors. It has been shown that the salts [QH]PF6 and [QH]BF4 undergo an order–disorder solid–solid phase transition to plastic phases, whereas [QH]2 SO4 ·H2 O and [QH]BPh4 do not display any plastic phase transition. Doping [QH]BF4 into the [QH]PF6 lattice up to 30% results in the formation of a solid solution that is plastic in an expanded thermal range, thanks to a phenomenon that we describe here for the first time as "reordering frustration".